2022
DOI: 10.3390/nu14122470
|View full text |Cite
|
Sign up to set email alerts
|

Edible Flowers as a Source of Dietary Fibre (Total, Insoluble and Soluble) as a Potential Athlete’s Dietary Supplement

Abstract: Edible flowers have been gaining popularity among researchers, nutritionists and chefs all around the world. Nowadays, flowers are used to make food look and/or taste better; however, they are also a very good source of valuable nutrients (antioxidants, vitamins, proteins, fats, carbohydrates, macro and microelements). The aim of our study was to determine the content of dietary fibre and total protein in selected edible flowers; we also compared the nutritional content of petals, differentiating between the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…Apart from bioactive components, edible flowers can also be consumed as a source of dietary fiber. It has been shown that the total dietary fiber content of edible flowers can reach up to 62 g/100 g flower (db) [ 23 ]. However, as per authors’ search on Web of Science, Scopus and PubMed databases using keywords “butterfly pea flower”, “Clitoria ternatea flower”, “soluble dietary fiber”, “insoluble dietary fiber” and “total dietary fiber”, no published research work was found on dietary fiber content of butterfly pea flowers.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from bioactive components, edible flowers can also be consumed as a source of dietary fiber. It has been shown that the total dietary fiber content of edible flowers can reach up to 62 g/100 g flower (db) [ 23 ]. However, as per authors’ search on Web of Science, Scopus and PubMed databases using keywords “butterfly pea flower”, “Clitoria ternatea flower”, “soluble dietary fiber”, “insoluble dietary fiber” and “total dietary fiber”, no published research work was found on dietary fiber content of butterfly pea flowers.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon may be due to the heating for a long time, which resulted in protein oxidation and degradation (Duque-Estrada et al, 2019;Jiang et al, 2022). In addition, the protein content ranged from 24.23 to 28.18 g/100 g in this research, and these were higher than other freeze-dried edible flowers, such as Magnolia × soulangeana, Sambucus nigra L., and Robinia pseudoacacia (Jakubczyk et al, 2022).…”
Section: Protein Contentmentioning
confidence: 62%
“…Flowers contain a nutrient-rich nature and easy access to sap; therefore, aphids were attracted to flower saps. In addition, some aphid species were drawn to certain colors (Jakubczyk et al 2022). Herbs served as an alternative host for aphids in this present study.…”
Section: Discussionmentioning
confidence: 99%